Complex segregation analysis of nonsyndromic cleft lip/palate in amerindian/caucasian admixture populations from Colombia (2000)
ABSTRACT: The present study was undertaken to examine the pattern of inheritance of cleft lip and palate (CLP) in pedigrees ascertained from localities belonging to Cundiboyacense altiplano, Colombia. This population has long been known to be the result of the admixture between Amerindian/Spaniard communities five centuries ago. Ninety-eight extended and multigenerational pedigrees, constituted by 125 nuclear components and 651 records were analyzed. Nine hypothetical models were contrasted using likelihood ratio tests. The hypotheses of no familial transmission, multifactorial component compared against that of the existence of a major gene only, the existence of a recessive major gene, that of non major component in the mixed model and that of the non transmission of major effect (t1=12= t3) were rejected. In contrast, hypotheses postulating a major locus (dominant, codominant) and that of no polygenic component in the mixed model could not be rejected. The major gene model without restrictions in d was the most parsimonious. Thus far, the most parsimonious model is that of a major gene (dominant-codominant) without multifactorial effects. Thus, it must be emphasized that, at least in the Colombian communities, environmental components in predisposing to CLP, as has been pointed out in those hypothesis involving fungicides and some kind of avitaminosis, must be discarded and the genetic mendelian factors must be the focus of research.